India : Selected Issues. (IMF Staff Country Reports; Country Report, 2006)
This Selected Issues paper for India reports that rapid growth is presenting new challenges to macroeconomic policy, although ensuring the sustainability of this growth requires broad-based fiscal and structural reforms. Higher world oil prices present risks in both the near and medium term. In the short-term, higher oil prices combined with robust domestic demand threaten to push inflation higher. Over the longer-term, permanently higher oil prices can depress growth and widen fiscal imbalances, in particular if the economy is not allowed to adjust to new price levels.